Endogenous liquidity and capital reallocation - Wei Cui; Randall D. Wright; Yu Zhu (Bank of Canada, 2022)
We study economies where firms acquire capital in primary markets then retrade it in secondary markets after information on idiosyncratic productivity arrives. Our secondary markets incorporate bilateral trade with search, bargaining and liquidity frictions. We distinguish between full and partial sales (one firm gets all or some of the other's capital). Both exhibit interesting long- and short-run patterns in data that the model can match. Depending on monetary and credit conditions, more partial sales occur when liquidity is tight. Quantitatively, we find significant steady-state and business-cycle implications. We also investigate the impact of search, taxation and persistence in firm-specific shocks.
Keywords: E22; E44; 330; Monetary policy; Business fluctuations and cycles